Effects of Dietary Tea Powder on the Growth Performance, Carcass Traits, and Meat Quality of Tibetan Pig × Bama Miniature Pigs - Zhaoming Yan; Yinzhao Zhong; Yunju Yin; Yehui Duan; Wenlong Wang; Lingyu Zhang; Qiuping Guo; Qinghua Chen; Fengna Li (Animals, 2021)
This study was conducted to evaluate the effects of tea powder in diets on the growth performance, meat quality, muscular amino acid, fatty acid profile, and serum biochemical indices of pigs. A total of 120 local Chinese pigs (Tibetan × Bama miniature pigs) were randomly assigned to five treatment groups, each with six pens and four pigs per pen. During a 60-day experiment, these groups of pigs were fed the normal diet and the diet supplemented with 1%, 2%, 4%, and 6% tea powder, respectively. The results showed that the supplementation of tea powder did not affect the growth performance of pigs. However, the dietary tea powder inclusion decreased (p < 0.05) the average fat thickness, total fat, and abdominal fat, and increased (p < 0.05) the total muscle as well. In addition, the dietary 2% tea powder decreased (p < 0.05) the muscle lightness (L*) and yellowness (b*). Compared with the control group, the dietary supplementation with 1%, 2%, and 4% tea powder raised (p < 0.05) the total amino acids (TAA) and essential amino acids (EAA), and dietary 4% and 6% tea powder increased (p < 0.05) the C20:5n3 in the muscle tissue. Furthermore, the serum lipid metabolism-related biochemical indices and mRNA expression levels were improved with the addition of tea powder. These results indicated that dietary tea powder might improve the carcass traits and meat quality of the Chinese native finishing pigs, but it does not affect their growth performance. Tea powder could be fully developed and reasonably applied as a dietary supplement.